Evaluation of the GeneXpert MTB/RIF to diagnose tuberculosis in a public health laboratory - Arbués, Mohanna Damasceno (2024)
OBJECTIVES: To evaluate the performance of geneXpert MTB/Rif versus conventional methods (bacilloscopy and culture) in the diagnosis of tuberculosis in a Central Public Health Laboratory (LACEN, Tocantins), Northern Brazil. METHODS: Retrospective study, with information from 1,973 suspected cases of tuberculosis from patients treated from January 2015 to December 2020. RESULTS: From the culture (reference standard), the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the geneXpert MTB/Rif were 100%, 97%, 74%, 100%, and 97%, respectively, against 85%, 98%, 80%, 98%, and 97% of bacilloscopy. CONCLUSIONS: The geneXpert MTB/Rif performed similarly to culture and better than bacilloscopy. Although positive cases with negative culture should be evaluated with caution, its routine use is important for the early detection of tuberculosis.